Effluent Water is a Concern for Global Environment and Health - Iqbal, Muhammad Naeem; Ashraf, Asfa (International Journal of Alternative Fuels and Energy, 2024)
Effluent water, or wastewater discharged from industrial, agricultural, or domestic sources, is an escalating global environmental and health concern. Effluent water management is important both environmental conservation and public health. Untreated effluent water may transmit diseases, taint water supplies, and damage aquatic ecosystems. Furthermore, toxic compounds in effluent water can persist in the environment, posing long-term risks to humans and wildlife alike. In this issue, Ashraf et al. report an overview of heavy metals and pesticides in water bodies, their sources, impacts, and mitigation strategies for a better environment and public health. Educating communities about proper waste disposal and water conservation can minimize domestic effluent pollution and its consequences.